2022
DOI: 10.1002/acm2.13724
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence (AI) versus expert: A comparison of left ventricular outflow tract velocity time integral (LVOT‐VTI) assessment between ICU doctors and an AI tool

Abstract: Purpose The application of point of care ultrasound (PoCUS) in medical education is a relatively new course. There are still great differences in the existence, quantity, provision, and depth of bedside ultrasound education. The left ventricular outflow tract velocity time integral (LVOT‐VTI) has been successfully used in several studies as a parameter for hemodynamic management of critically ill patients, especially in the evaluation of fluid responsiveness. While LVOT‐VTI has been broadly used, valuable appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 33 publications
0
4
0
1
Order By: Relevance
“…The study included a small number of tests that were measured by the auto LVOT-VTI tool (n = 46) as a secondary objective of the research, and unlike our study, compared the auto tool’s measurements to measurements conducted by relatively novice operators. The study has shown good agreement between a manual examination and the auto LVOT-VTI tool in the Venue™ device [ 28 ]. All in all, the issue of real time POCUS measuring tools has not yet been thoroughly studied.…”
Section: Discussionmentioning
confidence: 99%
“…The study included a small number of tests that were measured by the auto LVOT-VTI tool (n = 46) as a secondary objective of the research, and unlike our study, compared the auto tool’s measurements to measurements conducted by relatively novice operators. The study has shown good agreement between a manual examination and the auto LVOT-VTI tool in the Venue™ device [ 28 ]. All in all, the issue of real time POCUS measuring tools has not yet been thoroughly studied.…”
Section: Discussionmentioning
confidence: 99%
“…The results suggest that beginners may have taken longer to perform manual measurements due to uncertainty and technical inexperience. Although echocardiographic studies using AI have reported its usefulness as an image acquisition guide for inexperienced beginners and as an educational and diagnostic aid [14,27], the automatic measurement used in this study may also be useful for beginners. The automatic measurement used in this study can also be used by beginners as a guide for automatic analysis itself, which may allow for a faster examination and more efficient skills training.…”
Section: Discussionmentioning
confidence: 99%
“…It can also help standardize image acquisition and measurements. 1,6 In this way, it would be a tool used to optimize training and echocardiographic studies, 5,25,26 with the possibility of acquiring images of diagnostic quality comparable to those acquired manually by experts. 5,19,20,[22][23][24] The technology is applicable in clinical practice, in emergencies, and in remote areas with scarce resources and few experienced professionals.…”
Section: Image Acquisitionmentioning
confidence: 99%